Persistence Property and Estimate on Momentum Support for the Integrable Degasperis-Procesi Equation - Zhengguang Guo; Liangbing Jin (Abstract and Applied Analysis)
It is shown that a strong solution of the Degasperis-Procesi equation possesses persistence property in the sense that the solution with algebraically decaying initial data and its spatial derivative must retain this property. Moreover, we give estimates of measure for the momentum support.